Prognostic significance of castrate testosterone levels for patients with intermediate and high risk prostate cancer - Ozyigit, Gokhan (World J Clin Oncol, 2019)
BACKGROUND: Testosterone level of < 50 ng/dL has been used to define castrate level after surgery or after androgen deprivation treatment (ADT) in metastatic prostate cancer (PC). AIM: To evaluate the effect of two different castrate testosterone levels, < 50 and < 20 ng/dL, on biochemical relapse free survival (BRFS) in patients with non-metastatic intermediate and high risk PC receiving definitive radiotherapy (RT) and ADT. METHODS: Between April 1998 and February 2011; 173 patients with intermediate and high risk disease were treated. Radiotherapy was delivered by either three-dimensional-conformal technique to a total dose of 73.4 Gy at the ICRU reference point or intensity modulated radiotherapy technique to a total dose of 76 Gy. All the patients received 3 mo of neoadjuvant ADT followed by RT and additional 6 mo of ADT. ASTRO Phoenix definition was used to define biochemical relapse. RESULTS: Median follow up duration was 125 months. Ninety-six patients (56%) had castrate testosterone level < 20 ng/dL and 139 patients (80%) had castrate testosterone level < 50 ng/dL. Both values are valid at predicting BRFS. However, patients with testosterone < 20 ng/dL have significantly better BRFS compared to other groups (P = 0.003). When we compare two values, it was found that using 20 ng/dL is better than 50 ng/dL in predicting the BRFS (AUC = 0.63 vs 0.58, respectively). CONCLUSION: Castrate testosterone level of less than 20 ng/dL is associated with better BRFS and is better in predicting the BRFS. Further studies using current standard of care of high dose IMRT and longer ADT duration might support these findings.